Intraocular pressure: The effect of optional fasting & association with fluid & fat status - Yusof, Firdaus; Raihan, ENur; Mohd-Shukri, Nor Azwani (2016)
Introduction: Religious fasting has been shown to reduce intraocular pressure (IOP), as compared to during non-fasting period. This has been suggested to be associated with the reduction of total body water and body fat, as well as reduced intakes of fluid and dietary fat. Hence, this study aims: i) to compare the IOP between fasting and non-fasting periods, and ii) to assess the association of the IOP with total body fluid, body fat, and consumption of fluid and fat. Methods & materials: A cross-sectional study will be conducted amongst healthy, 20-30 years individuals (n=22), without any visual problems. Ethical approval and patient consent will be obtained prior to study commencement. Participants will be asked to perform optional fasting for one day (from dawn till dusk). During fasting, IOP will be measured using tonopen three times (morning, noon, and late afternoon), and after breaking of fast (evening). Total body fluid and body fat will be assessed by using Tanita body composition analyser. Intake of fluids and total fat will be estimated by using diet recall method. The same protocol will be repeated with participants during a non-fasting day. Results will be compared between fasting and non-fasting periods. Expected Results: It is expected for the IOP of participants to be reduced during fasting period compared to non-fasting period. This may be associated with lower total body fluid, body fat, as well as reduced intakes of fluid and total fat. Conclusion: Fasting may confer benefits in comanagement of eye diseases that cause detrimental increment of IOP.